CONSTRUCTION PROJECT CONTROL ANALYSIS USING EARNED VALUE MANAGEMENT, EARNED SCHEDULE MANAGEMENT, EARNED DURATION MANAGEMENT - Azaria Andreas; Nuryani Tinumbia; Erica Anggraini (Jurnal Infrastruktur, 2023)
Appropriate control methods are needed to anticipate potential problems and make construction projects better managed to improve efficiency, productivity, and quality of work. Earned Value Management (EVM) experienced problems in predicting duration because it used two scopes, namely cost and schedule. Then there is Earned Schedule Management (ESM) which monitors project performance through project schedules, but in its application ESM still uses variable costs for its indicators. To make up for the shortcomings of EVM and ESM, another method was developed by Khamooshi and Golafshani, namely Earned Duration Management (EDM) a method for measuring or estimating duration by separating the dimensions of schedule and cost. The purpose of this study is to determine the inaccuracies of the control methods of EVM and ESM in estimating EAC (Estimated At Completion) so that it requires EDM to estimate it. In this research, data collection was carried out in weeks 32 to 59. The data collected in the field was actual project work progress data, actual project financial data, and master plan data. The analysis of Schedule Varian (SV) and Schedule Varian time SV(t) variants shows negative values that result in an estimate of the final duration of the project that is late from the plan inversely proportional to dv which is positive value, meaning that the project is in accordance with the plan. Then the Schedule Performance Index (SPI) and Schedule Performance Index time SPI(t) show a value that is less than one which indicates the project is slower than scheduled, in contrast to the DPI it produces a value equal to one which means the project is in accordance with the plan. The EDM method generates an accurate trend in providing an assessment of the performance of project execution time compared to EVM and ESM. The contribution from research results comparing 3 methods shows that the EVM method produces anomalies in schedule control analysis, so that these deficiencies can be directed towards using the ESM method. while the EDM method, which is less familiar, is more appropriate for use in certain construction cases such as analysis of determining the amount of a claim.